COMPAÑIA DE PRODUCTOS FRITOS "BOCAOS" LTDA. - Angulo Olaya, Myriam (1992)
Family business in the food industry managed by five of nine siblings is experiencing declining sales and rising costs. A board of partners must set new directions and policies for the future. The case begins by describing the origin of the problem and then makes a historical account of the development of the company during its 24 years of existence. It exposes the factors and situations that generated its current structure, both internal and its environment. The objective is to awaken in business administration students, particularly in marketing, an analytical and research capacity that will allow them to broaden and deepen their knowledge of topics such as the decision-making process in marketing, new procedures or innovation of existing ones with respect to the management of the elements of the marketing mix, design of strategic plans and marketing programs that guarantee the permanence of an organization. Finally, the case shows the economic, social and political aspects of the environment in which the company operates.